2008
DOI: 10.1074/jbc.m804364200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Control of Phenoloxidase-induced Melanin Synthesis in an Insect

Abstract: The melanization reaction induced by activated phenoloxidase in arthropods must be tightly controlled because of excessive formation of quinones and excessive systemic melanization damage to the hosts. However, the molecular mechanism by which phenoloxidase-induced melanin synthesis is regulated in vivo is largely unknown. It is known that the Spätzle-processing enzyme is a key enzyme in the production of cleaved Spätzle from pro-Spätzle in the Drosophila Toll pathway. Here, we provide biochemical evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
186
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(197 citation statements)
references
References 40 publications
(52 reference statements)
10
186
0
1
Order By: Relevance
“…4D). As noted in other studies (16,22,27,28,38), these results showed that PPO and PO did not elute from the column at their predicted masses due to binding to other proteins and/or the column matrix. However, these data did show that melanization activity localized primarily to fraction 1, which contained little monomeric PO.…”
Section: B Mori Ppo Is Rapidly Processed After Collection From a Woundsupporting
confidence: 85%
See 3 more Smart Citations
“…4D). As noted in other studies (16,22,27,28,38), these results showed that PPO and PO did not elute from the column at their predicted masses due to binding to other proteins and/or the column matrix. However, these data did show that melanization activity localized primarily to fraction 1, which contained little monomeric PO.…”
Section: B Mori Ppo Is Rapidly Processed After Collection From a Woundsupporting
confidence: 85%
“…5B showed that processing of PPO to PO is associated with the rapid formation of many PO-containing bands in plasma that are chemically cross-linked and larger than monomeric PO, whereas our gel filtration data indicated that one of these complexes elutes in fraction 1, which also exhibits most of the melanization activity. Earlier studies with B. mori, T. molitor, and H. diomphalia (16,22,27,28,38) had already noted that processing of PPO to PO results in formation of PO-containing complexes that are chemically cross-linked. Adding a catecholamine substrate to a complex containing PO and SPH1 from T. molitor further increased its mass (27), whereas adding PTU to B. mori plasma inhibited the formation of most POcontaining bands (22).…”
Section: B Mori Ppo Is Rapidly Processed After Collection From a Woundmentioning
confidence: 99%
See 2 more Smart Citations
“…Melanization is employed to encapsulate and kill invading pathogens and is initiated upon pathogen detection (16). Recognition proteins in the insect hemolymph recognize non-self biomolecules and activate a clip domain serine proteinase cascade (17)(18)(19)(20). This cascade culminates in the activation of prophenoloxidase-activating proteinases, which convert prophenoloxidase to phenoloxidase (21)(22)(23).…”
mentioning
confidence: 99%